Trajectory tracking for autonomous underwater vehicle: An adaptive approach. (15th January 2019) - Guerrero, J.; Torres, J.; Creuze, V.; Chemori, A.
Abstract: During missions at sea, underwater vehicles are exposed to changes in the parameters of the system and subject to persistent external disturbances. These issues make the design of a robust controller a quite challenging task. This paper focuses on the design of an adaptive high order sliding mode controller for trajectory tracking. The main feature of the proposed control law is that it preserves the advantages of robust control. Moreover, it does not need the knowledge of the upper bound of the disturbance and it is easy to tune in real applications. Using Lyapunov concept, asymptotic stability of the closed-loop tracking system is ensured. The robustness of the proposed controller for trajectory tracking in depth and yaw dynamics is demonstrated through real-time experiments.